Analyses of the Disease Spectrum of Children After the Lushan Earthquake. Issue 7 (July 2015) - Ding, Hui; Fan, Haojun; Lv, Qi; Liu, Ziquan; Zhang, Yongzhong; Hou, Shike
<x xml:space="preserve">Abstract</x> An earthquake with a magnitude of 7.0 struck Lushan in Sichuan Province in China on April 20, 2013. Uniformed pediatricians visited the area where the epicenter was located to provide emergency relief care for children 10 days after the earthquake. Objectives The aims of the study were to analyze the features of the disease spectrum of children in Baoxing at early time after Lushan earthquake and to provide basis information, which will be useful for the arrangement of the medical resources of pediatrics in the medical relief after Lushan earthquake in similar situation in the future. Methods A total of 220 case files were classified and analyzed. These files provided information regarding pediatric patients whose conditions were diagnosed and treated in the mobile hospital established by the Affiliated Hospital of Logistical University of Chinese People's Armed Police Forces in Baoxing from April 20, 2013 to April 30, 2013. The demographic data of all these patients were collected and the disease spectrum was analyzed. Results Children's ages differed. A total of 59 patients were neonates, infants, and toddlers (27%); 111 were school-aged children (50%) and 50 were adolescents (23%). Common diseases and injuries include respiratory tract infection, dermatosis, and trauma, which were observed 10 days after the earthquake. Trauma was mainly accidental injury. The morbidity rate of infectious diseases was low. Conclusions Pediatricians have an important role in the early treatment and subsequent control of infectious diseases during earthquakes.